1979
DOI: 10.1677/joe.0.0810135
|View full text |Cite
|
Sign up to set email alerts
|

Ultradian and Circadian Rhythms in the Plasma Concentration of Cortisol in Sheep

Abstract: Three Merino ewes, adapted for about 3 weeks to their environment, were bled at 10 min intervals through a jugular venous cannula. Radioimmunoassay of plasma samples for cortisol revealed marked diurnal variations with peak levels just after midnight and lowest values in the afternoon. This rhythm appeared to result from a changing amplitude associated with a distinct ultradian rhythm (frequency 0.8-1.2 cycles/h) in the plasma level of cortisol. Calculation of the daily rate of secretion of cortisol from the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
57
0
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 0 publications
11
57
0
1
Order By: Relevance
“…A similar feature was also noted by Ravault and Ortavant (1977) The pattern of cortisol spikes showed that the main difference between the two photoperiods was in the size of the peaks rather than in their frequency. The mean number of episodes compares closely with that observed by Fulkerson and Tang (1979) Forbes, 1982) and active immunisation against prolactin depresses growth (Ohlson et al, 1981) there has been a report of a photoperiodic effect on growth in cattle in which prolactin was very low due to low environmental temperatures (Peters et al, 1980 …”
supporting
confidence: 70%
See 1 more Smart Citation
“…A similar feature was also noted by Ravault and Ortavant (1977) The pattern of cortisol spikes showed that the main difference between the two photoperiods was in the size of the peaks rather than in their frequency. The mean number of episodes compares closely with that observed by Fulkerson and Tang (1979) Forbes, 1982) and active immunisation against prolactin depresses growth (Ohlson et al, 1981) there has been a report of a photoperiodic effect on growth in cattle in which prolactin was very low due to low environmental temperatures (Peters et al, 1980 …”
supporting
confidence: 70%
“…Cortisol shows marked, frequent peaks and secretory spikes were defined using criteria similar to those described by Fulkerson and Tang (1979) for ovine cortisol secretion, that is when the plasma concentration in a sample was as least 10 nmol/I higher than that of the previous sample and the following sample also showed a level which was above the initial one. The end of an episode was when the concentration fell to at least as low as the pre-peak level in two consecutive samples.…”
mentioning
confidence: 99%
“…This is further supported by our observations of the willingness of the ewes to enter the milking parlor, the lack of cluster falls, and the presence of rumination during machine milking. The increase of basal levels during the day could be a result of increasing stress of manipulation, however it is more likely due to a nycthemeral rhythm already described in ewes [6,21].…”
Section: Discussionmentioning
confidence: 84%
“…In ruminants, it was described in sheep (Fulkerson and Tang, 1979;Mesbah and Brudieux, 1982) but it is not very pronounced in cattle and some studies failed to show any diurnal rhythm (see Mormede et al, 2007 for discussion). In the present study with goats, there was no clear-cut diurnal cycle, as previously shown by others (Kokkonen et al, 2001;Alila-Johansson et al, 2003).…”
Section: Discussionmentioning
confidence: 99%